The effect of Trim5 polymorphisms on the clinical course of HIV-1 infection. - Daniëlle van Manen (Public Library of Science (PLoS), 2008)
The antiviral factor tripartite interaction motif 5alpha (Trim5alpha) restricts a broad range of retroviruses in a species-specific manner. Although human Trim5alpha is unable to block HIV-1 infection in human cells, a modest inhibition of HIV-1 replication has been reported. Recently two polymorphisms in the Trim5 gene (H43Y and R136Q) were shown to affect the antiviral activity of Trim5alpha in vitro. In this study, participants of the Amsterdam Cohort studies were screened for polymorphisms at amino acid residue 43 and 136 of the Trim5 gene, and the potential effects of these polymorphisms on the clinical course of HIV-1 infection were analyzed. In agreement with the reported decreased antiviral activity of Trim5alpha that contains a Y at amino acid residue 43 in vitro, an accelerated disease progression was observed for individuals who were homozygous for the 43Y genotype as compared to individuals who were heterozygous or homozygous for the 43H genotype. A protective effect of the 136Q genotype was observed but only after the emergence of CXCR4-using (X4) HIV-1 variants and when a viral load of 10(4.5) copies per ml plasma was used as an endpoint in survival analysis. Interestingly, naive CD4 T cells, which are selectively targeted by X4 HIV-1, revealed a significantly higher expression of Trim5alpha than memory CD4 T cells. In addition, we observed that the 136Q allele in combination with the -2GG genotype in the 5'UTR was associated with an accelerated disease progression. Thus, polymorphisms in the Trim5 gene may influence the clinical course of HIV-1 infection also underscoring the antiviral effect of Trim5alpha on HIV-1 in vivo.